The Influence of Investment, Net Exports, and Labor on GRDP in the Manufacturing Industry Sector in Kalimantan - Pratama, Adhy Satya; Yusrie, Yusrie; Devi, Charitin; Darmawanto, Agus Tri; Ariani, Ariani; Shalahuddin, Shalahuddin (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the Effect of Investment (PMA), (PMDN), Net Exports, and Labor Partially and Simultaneously on GRDP of the Manufacturing Industry Sector in Kalimantan. The instrument used in this study is secondary data, collected from 2017 to 2024, with 40 data points. This study uses panel data regression analysis, which combines time-series and cross-sectional data. The Research Results partially indicate that the PMA, Net Exports, and Labor Variables do not have a significant effect. In contrast, PMDN does have a substantial effect on GRDP of the Manufacturing Industry Sector in Kalimantan during 2017-2024. While simultaneously showing that the PMA, PMDN, Net Exports, and Labor Variables have a significant effect on GRDP of the Manufacturing Industry Sector in Kalimantan in 2017-2024.